A Needs Analysis of Digital Comics for Islamic Education: Insights from Primary School Teachers in Kuala Lumpur - Nurjannah Binti Hasmad; Abdul Muhsien Sulaiman; Abdulrahman Alosman (Jurnal Pendidikan Agama Islam, 2025)
Purpose – The aim of this research is to determine the need for developing a digital comic aligned with the Islamic Education textbook. This study is a needs analysis based on discrepancy model that also employs the Technology Acceptance Model (TAM) used to determine Islamic education teachers’ acceptance towards the use of comic in the Islamic Education subject. Design/methods/approach – This is a quantitative  research. To obtain the data, some questionnaires were administered to 315 Islamic Education teachers  of public primary schools in Kuala Lumpur, Malaysia Findings – Descriptive analysis revealed strong pedagogical beliefs about the educational value of comics, positive attitudes, and high levels of acceptance regarding educational comics. Correlation analysis showed that teachers’ pedagogical beliefs about the educational value of comics, attitudes, and acceptance were all positively related, with attitudes most strongly associated with both perceived usefulness and ease of use. Regression results further demonstrated that attitudes were the strongest predictor of perceived usefulness, while pedagogical belief about comics’ educational role and current usage contributed more to perceived ease of use. Despite these positive perceptions, many teachers reported limited prior experience in using comics, signaling a gap between readiness and practice. Research implications/limitations – Teachers’ strong interest highlights the need for curriculum-aligned digital comics that should be supported by practical training, such as hands-on workshops that build confidence and ease of use. Additionally, policymakers and school leaders can accelerate adoption by embedding digital comics into teaching guidelines, resource repositories, and ICT initiatives. Originality/value – The research provides a base towards creating a comic-form learning source for Islamic Education subject.